Assessing the impact of intrinsic and extrinsic motivators on smart green IT device use: Reference group perspectives. Issue 1 (February 2015) - Koo, Chulmo; Chung, Namho; Nam, Kichan
Highlights We investigate the determinants of behavior intention to use green IT device. We tried to understand motivation theory in explaining the causal relationship between motivation aspects and perceived usefulness. We emphasized on how the reference group moderates the motivations and perceived usefulness relationship. Intrinsic motivation (perceived enjoyment) is significantly related to the perceived usefulness. Extrinsic motivation (saving money, legislative pressure) is strongly related to the perceived usefulness.